Extraction, Purification, Optimization, and Application of Galactomannan-Based Edible Coating Formulations for Guava Using Response Surface Methodology - Ammara Ainee; Sarfraz Hussain; Muhammad Nadeem; Asaad R. Al-Hilphy; Azhari Siddeeg (Journal of Food Quality)
Galactomannan from fenugreek and guar seeds were extracted, purified, and used in edible coatings, optimized via response surface methodology. The results showed that the emulsifying capacity and stability of fenugreek galactomannan (FG) and guar galactomannan (GG) increased with increase in the concentration of galactomannan up to 0.5–1%. The average optimized values of FG and GG in edible coatings were predicted to be 1.71% and 2.11% for weight loss, 0.72% and 2.14% for firmness, 1.02% and 1.44% for TSS, 0.83% and 1.36% for pH, 1.03% and 1.44% for acidity, respectively. Significant decrease in weight loss and maximum retention of firmness was observed in coated guava. The TSS increased up to a certain storage period in all treatments and decreased as the storage period progressed, whereas pH exhibited an increasing trend while a significant decrease in acidity was observed. The findings revealed that the shelf life of guava could considerably be improved by incorporating 1.24% galactomannan from GG and 1.01% from FG in the edible coating.